Comparing multi-criteria decision analysis to group negotiations in fisheries co-management. (April 2022) - Hayes, Christopher; Wainger, Lisa
Abstract: Chesapeake Bay oyster ( Crassostrea virginica ) management is often contentious due to differences in stakeholders' support for alternative strategies that aim to reverse historic declines in oyster harvests and abundance. The OysterFutures (OF) research program brought 16 stakeholders from the fishing industry, non-governmental organizations, and state and federal management agencies together to generate a consensus package of management recommendations for the Choptank River basin (a tributary of the Chesapeake Bay). In this study, we looked for group effects on results by testing the consistency of the OF group-negotiated management recommendations with individual preferences, as evaluated through individual interviews and multi-criteria decision analysis methods (MCDA). We further tested the sensitivity of option rankings to stakeholder group composition, preference elicitation method, and MCDA analytic choices. We developed metrics of cost-effectiveness and elicited time preferences for outcomes, which were only used implicitly in the negotiated OF process. We found that group effects appeared minimal since the OF-derived set of preferred options generally ranked highly in the MCDA analysis. However, some of the recommended options were not found to be among the most cost-effective. The consistency of findings using individual vs group-derived preferences suggests that methods to elicit individual preferences outside of group meetings might complement and streamline consensus-seeking engagement processes by quickly identifying areas of agreement and disagreement to reduce the substantial time commitments of in-person meetings.